The Niche Model of Defense Industry Analysis: Seeking The Suffiency of Indonesia’s Needs Main Equipment and Weaponery System (Alutsista) - Saputra, Rizki Marman; Somantri, Gumilar Rusliwa; Subroto, Athor; Marsetio (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
The niche industry model in Indonesia's defense industry refers to the development and specialization strategies adopted by defense companies in the country. In response to global dynamics and national defense needs, this model emphasizes focusing on specific market segments or technologies to achieve competitive advantages. This study explains how the niche industry model can enhance the competitiveness of Indonesia's defense industry through specialization in the development, production, and marketing of products or services tailored to specific defense needs. The analysis of this niche industry model involves evaluating various aspects, including technological sustainability, price competitiveness, security, and the ability to meet specific military needs. In the context of Indonesia, where the defense budget is limited, this model creates opportunities for local companies to focus on specific areas such as non-traditional weapon systems, intelligence technology, or cyber security equipment. The success of the niche industry model in Indonesia's defense industry is also closely related to collaborative efforts between the government, industry, and research institutions. This synergy facilitates the exchange of information, resources, and policy support necessary to foster technological development and innovation within this framework. While the niche industry model offers potential competitive advantages, challenges such as developing high-quality human resources, policy changes, and risk management need to be addressed. This study provides an in-depth view of the niche industry model in the context of Indonesia's defense industry, highlighting the opportunities and challenges faced and providing recommendations to support the sustainability and growth of this sector.